Influence of the Requisition of Specialized Teachers on Students' Learning Outcomes in Magarini, Kilifi County, Kenya - Maitha, Onesmus; Thinguri, Ruth (African Journal of Education and Practice, 2023)
Purpose: Education is seen as a remedy for all evils in each community due to its importance. The drive of this investigation was to explore schools' management practices on students' learning outcomes in public secondary schools in Magarini, Kilifi County, Kenya Methodology: The study was guided by the School Management and the Education Production Functions theories. The investigation assumed a mixed method and simultaneous triangulation design with descriptive quantitative survey design. The target population was 15,444 consisting of 100 teachers, 20 head teachers, 14,523 students, 800 parents, and 1 sub-county director of education. The sample was 390 participants which included 40 teachers, 20 head teachers, 249 students, 80 parents, and 1 sub-county director of education. The sampling techniques were census for the for the principals, random sampling for teachers, students and parents. The sub county director of education was sampled purposively. Questionnaire was used for teachers and while interviews were conducted on principals and sub county director of education. Quantitative data was analyzed in descriptive statistics and presented in tables, percentages and frequencies. Qualitative data was analyzed in themes and verbatim citations. Findings: From the findings, it was generally agreed that the requisition of specialized teachers had influence on the students' learning outcomes indicating that the presence of teachers was key to students' learning outcomes. There was no significant establishment of staff gap, meaning that the students' learning outcomes could not be possible. The issue of requisition of trained teachers from the TSC was not seen. Unique Contribution to Theory, Practice and Policy: The School Management and the Education Production Functions theories were used. The first theory was about involving series of activities relevant to the highly organized and effectual application of resources within the organization in order to attain organizational objectives. The second theory explained that the amount of output depended on the number of inputs and effort in due consideration of constraints dependent upon underlying technical processes. In schools the production functions were articulated in a functional form. The theories contributed to the study in that, good management practices could result into good outcomes. And individuals played part in making good results. Putting in place inputs so that outputs could be achieved was necessary. The study established that there was need for specialized teachers' requisition. These theories were validated in that there was need to employ good practices and put in place better inputs if good outcomes were expected.